Antibody Production in Murine Polymicrobial Sepsis—Kinetics and Key Players - Nicolai, Oliver; Pötschke, Christian; Schmoeckel, Katrin; Darisipudi, Murthy N.; van der Linde, Julia; Raafat, Dina; Bröker, Barbara M. (Frontiers in Immunology, 2020)
Although antigen-specific priming of antibody responses is impaired during sepsis, there is nevertheless a strong increase in IgM and IgG serum concentrations. Using colon ascendens stent peritonitis (CASP), a mouse model of polymicrobial abdominal sepsis, we observed substantial increases in IgM as well as IgG of all subclasses, starting at day 3 and peaking 2 weeks after sepsis induction. The dominant source of antibody-secreting cells was by far the spleen, with a minor contribution of the mesenteric lymph nodes. Remarkably, sepsis induction in splenectomized mice did not change the dynamics of the serum IgM/IgG reaction, indicating that the marginal zone B cells, which almost exclusively reside in the spleen, are dispensable in such a setting. Hence, in systemic bacterial infection, the function of the spleen as dominant niche of antibody-producing cells can be compensated by extra-splenic B cell populations as well as other lymphoid organs. Depletion of CD4+ T cells did not affect the IgM response, while it impaired IgG generation of all subclasses with the exception of IgG3. Taken together, our data demonstrate that the robust class-switched antibody response in sepsis encompasses both T cell-dependent and -independent components.